Anti-angiogenic and antioxidant effects of axitinib in human retinal endothelial cells: implications in diabetic retinopathy - Lazzara, Francesca; Conti, Federica; Sasmal, Pradip K.; Alikunju, Shanavas; Rossi, Settimio; Drago, Filippo; Platania, Chiara Bianca Maria; Bucolo, Claudio (Frontiers in Pharmacology, 2024)
Diabetic retinopathy is a secondary microvascular complication of diabetes mellitus. This disease progresses from two stages, non-proliferative and proliferative diabetic retinopathy, the latter characterized by retinal abnormal angiogenesis. Pharmacological management of retinal angiogenesis employs expensive and invasive intravitreal injections of biologics drugs (anti-vascular endothelial growth factor agents). To search small molecules able to act as anti-angiogenic agents, we focused our study on axitinib, which is a tyrosine kinase inhibitor and represents the second line treatment for renal cell carcinoma. Axitinib is an inhibitor of vascular endothelial growth factor receptors and among the others tyrosine kinase inhibitors (sunitinib and sorafenib) is the most selective towards vascular endothelial growth factor receptors 1 and 2. Besides the well-known anti-angiogenic and immunemodulatory functions, we hereby explored the polypharmacological profile of axitinib, through a bioinformatic/molecular modeling approach and in vitro models of diabetic retinopathy. We showed the anti-angiogenic activity of axitinib in two different in vitro models of diabetic retinopathy, by challenging retinal endothelial cells with high glucose concentration (fluctuating and non-fluctuating). We found that axitinib, along with inhibition of vascular endothelial growth factor receptors 1 (1.82 ± 0.10; 0.54 ± 0.13, phosphorylated protein levels in fluctuating high glucose vs axitinib 1µM, respectively) and vascular endothelial growth factor receptors 2 (2.38 ± 0.21; 0.98 ± 0.20, phosphorylated protein levels in fluctuating high glucose vs axitinib 1µM, respectively), was able to significantly reduce (p<0.05) the expression of Nrf2 (1.43 ± 0.04; 0.85 ± 0.01, protein levels in fluctuating high glucose vs axitinib 1µM, respectively) in retinal endothelial cells exposed to high glucose, through predicted Keap1 interaction and activation of melanocortin receptor 1. Furthermore, axitinib treatment significantly (p<0.05) decreased ROS production (0.90 ± 0.10; 0.44 ± 0.06, fluorescence units in high glucose vs axitinib 1µM, respectively) and inhibited ERK pathway (1.64 ± 0.09; 0.73 ± 0.06, phosphorylated protein levels in fluctuating high glucose vs axitinib 1µM, respectively) in HRECs exposed to high glucose. The obtained results about the emerging polypharmacological profile strengthen the hypothesis that axitinib could be a valid candidate to handle diabetic retinopathy, with ancillary mechanisms of action.